A Review of Guidelines for Diabetic Patients with Hypertension from Various Countries - Soon Hee Lee (Current Topics in Medicine and Medical Research Vol. 13, 2021)
Hypertension is a major complication associated with more than 50% of diabetic patients. Both diseases have a close pathophysiological relationship and are independent risk factors for cardiovascular disease. In patients with diabetes mellitus and hypertension, cardiovascular complications increase more than four times than in non-diabetic patients with normal blood pressure. Therefore, it is very important for diabetics to diagnose the occurrence of high blood pressure early and to treat it according to the blood pressure control goal. However, it is confused about what standards we should approach managing hypertension by looking at the numerous medical guidelines that have been released recently. Since each treatment guideline can vary depending on what evidence data is used and what level of evidence is adopted, interpretation of this is considered to be very important, but these guidelines cannot take precedence over the judgment of doctors who make clinical judgments considering various characteristics of individual patients.